Transformation of Education Institution in Industrial Era 4.0: Modern Management in Islamic Boarding School - Sulistiani, Dwi (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
The development of boarding schools both in terms of quantity and quality has increased in the last decade. In the industrial era 4.0, where technology has become essential in a borderless world, it requires Islamic boarding schools to start transforming to improve the quality of education services. The implementation of modern management by utilizing information technology has become a demand in the current era. Descriptive qualitative research with case study method aims to analyze Kyai's principles in contemporary management and the transformation of Islamic boarding schools, which reflected in modern management, which has been applied by Al Amien Islamic boarding school, Prenduan, Sumenep. This Islamic boarding school is one of the most influential boarding schools in Indonesia. The results of this study indicate there are eight principles held by Kyai and all of Al Amien Prenduan boarding school residents. These principles show the existence of modern thinking from Kyai in managing boarding schools, as well as efforts to transform boarding schools that integrate classic books with current thinking needed in the industrial era 4.0. Transformation of Al Amien Islamic boarding school is carried out by utilizing information technology in an online-based academic system, attendance of students with fingerprint, and accounting software in preparing financial statements. Besides, spending on santri at each profit center is done by using fingerprint to make it easier to supervise the expenditure of santri so that they are not accustomed to living wastefully. Modern management is proven to facilitate academic and non-academic management as well as increase accountability and transparency of financial reporting there.